Modelling the perception of security in the Covid-19 era - García Lirios, Cruz; Hernánez Valdés, Jorge; Molina González, María (Revista de Investigación Académica Sin Frontera: Facultad Interdisciplinaria de Ciencias Económicas Administrativas - Departamento de Ciencias Económico Administrativas-Campus Navojoa, 2021)
The objective of this work was to provide empirical validity to the Security Perception Scale. A cross-sectional, correlational and psychometric study was conducted with a selection of 100 students. He suspects his participation in local crime prevention programs. Seven dimensions were established: territorial, national, public (government), human, public (self-protection), private and international, although the research design limited the results to the sample surveyed, suggesting the extension of work to other aspects of public insecurity .